2005
DOI: 10.1039/b504737d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of picomolar levels of interleukin-8 in human saliva by SPR

Abstract: Researchers at UCLA have discovered that the levels of interleukin-8 (IL-8) protein in the saliva of healthy individuals and patients with oropharyngeal squamous cell carcinoma (OSCC) are 30 pM and 86 pM, respectively. In this study, we present the development of the first immunoassay for the quantification of picomolar IL-8 concentrations in human saliva using Biacore surface plasmon resonance (SPR) in a microfluidic channel. A sandwich assay using two monoclonal antibodies, which recognize different epitopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 14 publications
1
94
0
Order By: Relevance
“…In this context, the biomarkers, such as interleukin‐8 (IL‐8), interleukin‐6 (IL‐6), vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) are currently being used for detection of oral cancer 14, 15, 16, 17. The OC detection via these biomarkers is currently a challenge since these are secreted at very low concentration (≈pg mL −1 ) and the biosensors proposed for the detection of these biomarkers require serum samples and are thus invasive 14, 15, 16, 17. Thus, detection of OC biomarkers in human saliva samples provides a noninvasive and pain‐free alternative.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the biomarkers, such as interleukin‐8 (IL‐8), interleukin‐6 (IL‐6), vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) are currently being used for detection of oral cancer 14, 15, 16, 17. The OC detection via these biomarkers is currently a challenge since these are secreted at very low concentration (≈pg mL −1 ) and the biosensors proposed for the detection of these biomarkers require serum samples and are thus invasive 14, 15, 16, 17. Thus, detection of OC biomarkers in human saliva samples provides a noninvasive and pain‐free alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made for the detection of OC utilizing biosensor platforms 14, 15, 16, 17. Yang et al reported electrochemical biosensor for the detection of trace level of salivary IL‐8 protein 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, the LOD of enzyme linked immunosorbent assay (ELISA) for IL-8 in buffer is 1 pM (8.3 pg/mL, the molar molecular weight of IL-8 is 8.3 kDa) and SPR achieves an LOD of 184 pM (1.5 ng/mL ) for IL-8 in human saliva. 39 The LOD of ELISA for TNF-α was reported to be 0.48 pg/mL in the buffer. 40 Compared with other biosensors for the detection of IL-8 or TNF-α, our method has not only better sensitivity, but also multiplexed detection ability.…”
Section: Multiplexed Detection Of Oscc Biomarkers In Salivamentioning
confidence: 99%
“…9 However, the concentration of the biomarkers in saliva is much lower than that in the blood, and the salivary environment is more complicated, revealing that a sensitive and multiplexed detection method for biomarkers is highly required. 10 These biosensors based on the labeling of biomolecules with tags, such as radioactive isotope, quantum dots or fluorescent dyes, have been applied for the detection of disease biomarkers. [11][12][13][14] Although these label-based methods have good sensitivity, they suffer from some drawbacks, including challenges concerning the labeling procedures, tedious and time-consuming experimental procedures, thereby hindering them from more extensive applications.…”
Section: Introductionmentioning
confidence: 99%